Effects of rTMS treatment on global cognitive function in Alzheimer's disease: A systematic review and meta-analysis - Zhang, Tianjiao; Sui, Youxin; Lu, Qian; Xu, Xingjun; Zhu, Yi; Dai, Wenjun; Shen, Ying; Wang, Tong (Frontiers in Aging Neuroscience, 2022)
Abstract Background: Although repetitive transcranial magnetic stimulation (rTMS) has been extensively studied in patients with Alzheimer's disease (AD), the clinical evidence remains inconsistent. The purpose of this meta-analysis was to evaluate the effects of rTMS on global cognitive function in patients with AD. Methods: An integrated literature search using 4 databases (PubMed, Web of Science, Embase, and Cochrane Library) was performed to identify English language articles published up to October 6, 2021. We pooled Mini-Mental State Examination (MMSE) and Alzheimer’s Disease Assessment Scale-cognitive subscale (ADAS-Cog) scores using a random-effects model via RevMan 5.4 software. We calculated estimates of mean differences (MD) with 95% confidence intervals (CI). The primary outcomes were pre-post treatment changes in global cognition as measured using MMSE and ADAS-Cog immediately after rTMS treatment, and the secondary outcome was duration of cognitive improvement (1-1.5 and ≥3 months). Results: Nine studies with 361 patients were included in this meta-analysis. The results showed that rTMS significantly improved global cognitive function immediately following rTMS treatment ( [MD] 1.85, 95% confidence interval [CI] 1.57 to 2.12, p < 0.00001, MMSE; 2.72, 95% CI, 1.77 to 3.67, p < 0.00001, ADAS-Cog), and the therapeutic effects persisted for an extended duration (2.20, 95% CI, 0.93 to 3.47, p =0.0007, MMSE; 1.96, 95% CI, 0.96 to 2.95, p =0.0001, ADAS-Cog). Subgroup analyses showed that high frequency rTMS targeted to the left dorsolateral prefrontal cortex (DLPFC) for over 20 sessions induced the greatest cognitive improvement, with effects lasting for more than one month after the final treatment. There were no significant differences in dropout rate (p > 0.05) or adverse effect rate (p > 0.05) between the rTMS and control groups. Conclusions: Repetitive TMS is a potentially effective treatment for cognitive impairment in AD that is safe and can induce long-lasting effects. Our results also showed that ADAS-cog and MMSE differed in determination of global cognitive impairment.